Phenotypic expansion and further characterisation of the 17q21.31 microdeletion syndrome. Issue 7 (15th May 2009) - Tan, T Y; Aftimos, S; Worgan, L; Susman, R; Wilson, M; Ghedia, S; Kirk, E P; Love, D; Ronan, A; Darmanian, A; Slavotinek, A; Hogue, J; et al.
Abstract : Background: The recognition of the 17q21.31 microdeletion syndrome has been facilitated by high resolution microarray technology. Recent clinical delineation of this condition emphasises a typical facial appearance, cardiac and renal defects, and speech delay in addition to intellectual disability, hypotonia and seizures. Methods and results: We describe 11 previously unreported patients expanding the phenotypic spectrum to include aortic root dilatation, recurrent joint subluxation, conductive hearing loss due to chronic otitis media, dental anomalies, and persistence of fetal fingertip pads. Molecular analysis of the deletions demonstrates a critical region spanning 440 kb involving either partially or wholly five genes, CRHR1, IMP5, MAPT, STH, and KIAA1267. Conclusion: These data have significant implications for the clinical diagnosis and management of other individuals with 17q21.31 deletions.